2019
DOI: 10.1093/gigascience/giz129
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the 373k gene space of the polyploid sugarcane genome reveals reservoirs of functional diversity in the world's leading biomass crop

Abstract: Background Sugarcane cultivars are polyploid interspecific hybrids of giant genomes, typically with 10–13 sets of chromosomes from 2 Saccharum species. The ploidy, hybridity, and size of the genome, estimated to have >10 Gb, pose a challenge for sequencing. Results Here we present a gene space assembly of SP80-3280, including 373,869 putative genes and their potential regulatory regions. The alignment of single-copy genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 95 publications
3
95
0
9
Order By: Relevance
“…Sugarcane possesses one of the most complex genomes known among crops (O'Hara and Mundree, 2016;Mancini et al, 2018;De Souza Barbosa et al, 2020) which could, until recently, only be assembled at the scaffold level (Grativol et al, 2014;Okura et al, 2016;Riaño-Pachón and Mattiello, 2017;Souza et al, 2019). Only in 2018 did an approach coupling next-generation and long-read sequencing with high-throughput chromatin conformation capture enable a chromosome-and allele-level genome of a Ssp clone to be assembled (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sugarcane possesses one of the most complex genomes known among crops (O'Hara and Mundree, 2016;Mancini et al, 2018;De Souza Barbosa et al, 2020) which could, until recently, only be assembled at the scaffold level (Grativol et al, 2014;Okura et al, 2016;Riaño-Pachón and Mattiello, 2017;Souza et al, 2019). Only in 2018 did an approach coupling next-generation and long-read sequencing with high-throughput chromatin conformation capture enable a chromosome-and allele-level genome of a Ssp clone to be assembled (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study identified only CDS sequences of sugarcane circadian clock genes but not their genomic sequences due to the relatively few genomic sequences publicly available at that time for the sugarcane cultivar of interest, plus a high percentage of incomplete genomic sequences (Vicentini et al, 2012;de Setta et al, 2014). Here we used the SUCEST sequences (Hotta et al, 2013) to search for their genomic sequences in an unpublished sugarcane genomic database (Souza et al, 2019) We identified genomic contigs for ScLHY (previously identified as ScCCA1), ScTOC1, ScPRR73 (previously identified as ScPRR3) and ScPRR95 (previously identified as ScPRR59) ( Table S2). A new homolog, ScPRR37, was identified here for the first time in sugarcane (Table S2, Figure 1).…”
Section: Identification Of Alternatively Spliced Forms Of Sugarcane Cmentioning
confidence: 99%
“…It is possible that some of the alternative sequences we found are not AS events but different haplotypes since sugarcane is highly polyploid and aneuploid. To exclude this possibility, we obtained the sequences for circadian clock genes from four different sugarcane sequencing projects (Riaño-Pachón and Mattiello, 2017; Garsmeur et al, 2018;Zhang et al, 2018;Souza et al, 2019). We found 11 sequences for the 5′ portion of the ScLHY: 4 from S. spontaneum (Zhang et al, 2018), 6 from the commercial Saccharum hybrid SP80-3280 (Riaño-Pachón and Mattiello, 2017; Souza et al, 2019) and 1 from the commercial Saccharum hybrid R570 (Garsmeur et al, 2018).…”
Section: Identification Of Alternatively Spliced Forms Of Sugarcane Cmentioning
confidence: 99%
“…The genetic studies on the genus Saccharum (lato sensu) are complex because of the evidence of multiple cycles of past polyploidization events and consequent reticulate evolution, often followed by silencing and elimination of duplicated genes. Thus, phylogenetic reconstruction involving the genera close to Saccharum or even the Saccharum species, and especially the cultivated hybrids (Saccharum × officinarum) are challenging, especially if nuclear DNA sequences are used (Garsmeur et al, 2018;Zhang et al, 2018;Souza et al, 2019). Phylogenomics based on chloroplast genome (plastome) sequences may be a solution to overcome the difficulties imposed by polyploidy and aneuploidy, both found in the genus Saccharum (lato sensu), because the plastome is not affected by the ploidy level.…”
Section: Introductionmentioning
confidence: 99%